2016
DOI: 10.1016/j.scriptamat.2015.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of nanoscale intermetallic precipitates in highly neutron irradiated reactor pressure vessel steels

Abstract: Massive, thick-walled pressure vessels are permanent nuclear reactor structures that are exposed to a damaging flux of neutrons from the adjacent core. The neutrons cause embrittlement of the vessel steel that growswith dose (fluence), as manifested by an increasing ductile-to-brittle fracture transitiontemperature. Extending reactor life requires demonstrating that large safety margins against brittle fracture are maintained at the higher neutron fluence associated with beyond 60years of service.Here synchrot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(35 citation statements)
references
References 34 publications
6
25
0
Order By: Relevance
“…These clusters are presumably related to the formation of "late blooming" MNPs at high fluences (Odette, 1995). Applying a combination of methods, Sprouster et al (2016) confirmed that the MNPs identified after high-fluence irradiations are welldefined phases. Böhmert et al (2004) and Wagner et al (2012) reported pronounced linear correlations of the square root of precipitate volume fraction and irradiation hardening of RPV steels.…”
Section: Fe-cu Alloys and Reactor Pressure Vessel Steelsmentioning
confidence: 57%
“…These clusters are presumably related to the formation of "late blooming" MNPs at high fluences (Odette, 1995). Applying a combination of methods, Sprouster et al (2016) confirmed that the MNPs identified after high-fluence irradiations are welldefined phases. Böhmert et al (2004) and Wagner et al (2012) reported pronounced linear correlations of the square root of precipitate volume fraction and irradiation hardening of RPV steels.…”
Section: Fe-cu Alloys and Reactor Pressure Vessel Steelsmentioning
confidence: 57%
“…MNSPs, have been called late blooming phases (LBP), due to their slow nucleation and growth rates compared to CRPs [4][5][6][9][10][11][18][19][20][21]. However, MNSPs are now widely observed [25][26][27][28][29][30][31][32][33][34][35]. Further, recent models [36][37][38][39] support the early predictions of their evolutions as intermetallic phases.…”
Section: Introduction Background and Objectivementioning
confidence: 99%
“…The underprediction of embrittlement at high fluence is primarily attributed to the delayed formation of large volume fractions (f) of Mn-Ni-Si precipitates (MNSPs), which are not accounted for in current regulatory models [4][5][6][7][8]. The existence of MNSPs has been demonstrated in both surveillance and test reactor irradiations [4,[9][10][11][12][13][14][15][16][17][18][19][20][21][22], but their detailed character and formation mechanisms is one of the most highly debated issues in the field of radiation effects [4,14,[23][24][25][26]. The central question relates to the driving force for MNSP formation.…”
mentioning
confidence: 99%